Charactrization of follicular dynamicss and luteal function during short estrous cycle in suckled postpartum Mehsana buffaloes - AWASTHl, M K; KAVANI, F S; KAVANI, F S; SIDDIQUEE, G M; DHAMI, A J; PANCHAL, M T (The Indian Journal of Animal Reproduction, 2023)
The present study :Was aimed to characterize the pattern of follicular growth and progesterone concentratiod during. short estrous cycle in postpartum suckled water buffaloes. Twenty freshly calved Mehsana buffaloct were selected and. animals (n=3) showing short estrous cycle were scanned daily for ovarian follicular development .from day of first postpartum estrus to next using a real-time B-mode ultrasound scanner equipped with a 6.5 MHz convex linear array transducer. The blood samples were collected from each animal on Days 3, 7 and IO after first postpartum estrus for estimation of plasma levels of progesterone. These animals showed one-wave follicular growth during short estrous cycle and short luteal phase with mean plasma progesterone concentratiod of0.49, 0.80 and 0.26 ng/ml on Days 3, 7 and i o· post-estrus, respectively, suggesting subnormal functioning of , CL. It is concluded that short estrous cycle is characterized by one-wave. of follicular development observed in few animals during early postpartum period in suckled water buffaloes.